2021
DOI: 10.3390/educsci11070316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web-Based Autonomy-Supportive Intervention on Physical Education Teacher Outcomes

Abstract: The current study tested the efficacy of a web-based autonomy-supportive intervention program on changes in physical education (PE) teachers’ self-reports of autonomy support, psychological need satisfaction, intrinsic motivation, and teaching efficacy for students’ engagement. In this study, 101 secondary school PE teachers and their 652 students were randomized either to a web-based autonomy-supportive experimental group or to the control group. Manipulation checks indicated that the intervention was effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…This is important information for practitioners and researchers designing future interventions with the aim of increasing adolescents' PA and HRQoL. Specifically, previous research has highlighted that, when PE teachers become more supportive of autonomy in their students, both students [7,[49][50][51][52] and the teachers themselves [53,54] will gain various benefits. Based on this, future research should also test the intervention effects if parents and peers become more supportive of adolescents' autonomy.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…This is important information for practitioners and researchers designing future interventions with the aim of increasing adolescents' PA and HRQoL. Specifically, previous research has highlighted that, when PE teachers become more supportive of autonomy in their students, both students [7,[49][50][51][52] and the teachers themselves [53,54] will gain various benefits. Based on this, future research should also test the intervention effects if parents and peers become more supportive of adolescents' autonomy.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 99%
“…Based on students’ perceptions, several intervention studies have demonstrated that physical education teachers can effectively learn how to become autonomy-supportive [ 12 , 13 ]. Studies have also found that autonomy-supportive teaching is beneficial not only to students’ outcomes but to teachers themselves, who benefit from adopting an autonomy-supportive style [ 14 ]. Controlling teaching, on the other hand, limits students’ basic psychological needs and leads to the frustration of basic psychological needs and an inability to adapt [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future research should focus on investigating the effects of different autonomy-supportive teaching styles (i.e., organizational compared to procedural compared to cognitive autonomy support) on students’ adaptive outcomes. Lastly, PE teachers might learn to be more autonomy-supportive in vocational education; here, future research could also investigate the psychological effects on educators when teaching PE classes in an autonomy-supportive manner ( Tilga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%